Vitamin D Receptor Genetic Polymorphisms Associate With a Decreased Susceptibility to Extremity Osteomyelitis Partly by Inhibiting Macrophage Apoptosis Through Inhibition of Excessive ROS Production via VDR-Bmi1 Signaling - Zhao, Xing-Qi; Wan, Hao-Yang; He, Si-Ying; Qin, Han-Jun; Yu, Bin; Jiang, Nan (Frontiers in Physiology, 2022)
Background: Previous studies had reported that vitamin D receptor (VDR) gene polymorphisms were related to the development of several inflammatory disorders. However, potential links between such polymorphisms and risks of developing fracture related infection (FRI) and underlying mechanisms remain unclear. This study aimed to analyze potential associations between VDR genetic variations and susceptibilities to FRI in Chinese Han population and investigate potential mechanisms. Methods: Between January 2016 and December 2019, altogether 336 FRI patients and 368 healthy controls were genotyped of six VDR genetic polymorphisms, including ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570), TaqI (rs731236), GATA (rs4516035) and Cdx-2 (rs11568820), by the SNaPshot genotyping method. Then, male C57BL/6 mice were randomly divided into vitamin D-standard, -excess, -deficient and -rescued groups. One week after the model surgery, FRI occurrence and severity were assessed by bacterial count and histopathological staining. In vitro, the phagocytosis and apoptosis of macrophages, and bactericidal ability were evaluated by overexpression or knockdown of VDR protein. Results: Significant associations were found between rs7975232 and FRI development by recessive model (P = 0.019, OR = 0.530) and homozygous model (P = 0.018, OR = 0.515). Patients with AA genotype had significantly lower levels of tumor necrosis factor α (TNF-α) (8.1 vs. 10 vs. 20.2 pg/ml) and serum amyloid A (SAA) (14.6 vs. 32.2 vs. 32.5 mg/L), and a relatively higher level of serological vitamin D (22.1 vs. 20.3 vs. 18.4 ng/ml) than those of AC and CC genotypes. In vivo, the femoral bacterial load of vitamin D deficient mice was highest among the groups, with the most severe histopathological changes, and vitamin D supplementation partly reversed (P < 0.05). In vitro, active vitamin D promoted phagocytosis and sterilization of macrophages, and inhibited apoptosis during infection. ROS inhibitor inhibited apoptosis of macrophages. Active vitamin D inhibited excessive ROS production in macrophages via VDR-Bmi1 signaling pathway. Conclusions: In this Chinese cohort, ApaI associates with a decreased risk of FRI development, which may achieve partly by inhibiting macrophage apoptosis with inhibition of excessive ROS production via VDR-Bmi1 signaling pathway.